2019
DOI: 10.3390/nu11092103
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Vitamin C on Organ Function in Cardiac Surgery Patients: A Systematic Review and Meta-Analysis

Abstract: Background: Cardiac surgery is associated with oxidative stress and systemic inflammation, which both contribute to postoperative organ dysfunction. Vitamin C is a pleiotropic, antioxidant, and potentially organ-protective micronutrient. Past clinical trials and meta-analyses have focused predominantly on occurrence of postoperative atrial fibrillation. Therefore, we investigated the influence of perioperative vitamin C administration on clinically relevant parameters closer related to the patient’s recovery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…Our current metaanalysis was restricted to trials that tested vitamin C alone. A fourth recent meta-analysis concluded that vitamin C shortens ventilation time in cardiac surgery patients [50]; however, the study was shown to contain several substantial statistical errors [51].…”
Section: Discussionmentioning
confidence: 99%
“…Our current metaanalysis was restricted to trials that tested vitamin C alone. A fourth recent meta-analysis concluded that vitamin C shortens ventilation time in cardiac surgery patients [50]; however, the study was shown to contain several substantial statistical errors [51].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this conclusion is incorrect based on the evidence presented. This particularly small p-value from Figure 6 [2] is associated with the test of heterogeneity, not with the test of overall effect (p = 0.02, Z = 2.27). In the abstract, this same error occurs for ICU length of stay and hospital length of stay in that the reported p-values are from the heterogeneity tests, not from the tests of overall effect.…”
mentioning
confidence: 86%
“…. ventilation time (p < 0.00001)" [2]. We believe that this conclusion is incorrect based on the evidence presented.…”
mentioning
confidence: 88%
See 2 more Smart Citations